Response of cabbage to nitrogen fertilization in the northeastern region of Pará State - Da Silva Carvalho, Lívia Tálita (2018)
Low rates of N may result in low yield and small cabbage heads due to reduced leaf area. On the other hand, very high rates of N may favor excessive leaf growth, reducing sugar and Vitamin C contents and head dry matter. This work evaluates the influence of N rates on the development and production of cabbage. The experiment was conducted under field conditions at the Experimental Farm of Igarapé Açu (FEIGA), in the municipality of Igarapé Açu. The soil of the region is classified as Dystrophic Yellow Argisol, with sandy texture. The experimental design was randomized blocks, with five treatments and three replications. The treatments evaluated were Nitrogen rates (0; 90; 180; 270; and 360 kg ha-1) in the form of urea, applied in top dressing. The N rate that maximized cabbage head production (0.60 kg) was 249.5 kg N ha-1. The rate that maximized commercial yield (16883.81 kg ha-1) was 270.27 kg N ha-1.